Use of negative pressure wound therapy with instillation in the management of cervical necrotizing fasciitis. Issue 11 (6th August 2015) - Frankel, Jonathan K.; Rezaee, Rod P.; Harvey, Donald J.; McBeath, Evan R.; Zender, Chad A.; Lavertu, Pierre; Chen, Amy
ABSTRACT Background Cervical necrotizing fasciitis is an aggressive infection that can be rapidly fatal if aggressive therapies are not initiated early. Negative pressure wound therapy has been established as an effective tool in promoting wound healing, but its use in the acutely infected wound has been avoided because it limits frequent irrigations and standard dressing changes. Methods We discuss a novel application of negative pressure wound therapy with instillation in an immunocompromised patient with extensive cervical necrotizing fasciitis. Results The negative pressure wound therapy with instillation provided pain relief by minimizing the frequency of dressing changes, increased the speed of healing, helped to control infection, and facilitated the development of a healthy wound bed sufficient for reconstruction with a split thickness skin graft. Conclusion The role of negative pressure wound therapy with instillation continues to expand and can be used in the management of both acute and chronic wounds in the head and neck. © 2015 Wiley Periodicals, Inc. Head Neck 37: E157–E160, 2015